THE ROLE OF SOCIAL INTERACTION IN ENHANCING STUDENTS’ ONLINE LEARNING EXPERIENCE - Khong Eng Mun; Seow Ai Na; Lam Siew Yong (International Journal of Accounting, Finance and Business, 2023)
Online learning is increasingly recognised as an alternative to traditional face-to-face education in higher education. The absence of in-person contact in online learning prompts a need to explore how social interaction shapes the learning experience. This study delves into the critical role of social interaction in shaping the overall online learning experience. Through qualitative analysis, the researchers examine the experiences of five university students with exposure to both online and traditional learning methods. Thematic analysis identified key themes: The perceived benefits and drawbacks of online learning, the importance of social interaction with instructors and peers, the encouragement of interaction by the instructors, and satisfaction with student-instructor and student-student interaction. The implications of this study extend to educators, institutions, and policymakers, providing insights to optimise online learning environments. It emphasises the need for pedagogical advancements, flexible learning models, and technology integration in online education. This study contributes to the evolving field of online education, ensuring it remains effective and responsive to student needs in the digital age. Future research opportunities include exploring advanced pedagogical strategies, assessing the long-term effects of flexible learning models, and examining emerging technologies in online education.